DEVELOPMENT OF SNAKES AND LADDER GAME MEDIA TO IMPROVE STUDENTS' LITERACY AND NUMERACY SKILLS IN MATHEMATICS AT SD MUHAMMADIYAH BANYURADEN - Silvia Muna Rosida (Journal Informatic, Education and Management (JIEM), 2026)
The low literacy and numeracy skills of elementary school students are one of the problems that need attention in the mathematics learning process. Learning that is still dominated by lecture methods and the minimal use of innovative learning media causes students to be less active and experience difficulties in understanding the material. This study aims to develop a valid, practical, and effective educational snakes and ladders game media to improve the literacy and numeracy skills of fourth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 30 fourth-grade students of Muhammadiyah Banyuraden Elementary School as the experimental class and 30 fourth-grade students of Banyuraden Elementary School as the control class. Data collection techniques included interviews, observations, questionnaires, documentation, and tests. The results showed that the educational snakes and ladders game media obtained a validation score of 60 from material experts and 59 from media experts with a very good category. The results of the practicality test showed a teacher response of 45 and a student response of 8.5 with a very good category. The effectiveness test results showed a significant difference between the control class and the experimental class in literacy (sig. = 0.041) and numeracy (sig. = 0.046) skills. The paired sample t-test results also showed a significant increase in literacy and numeracy skills after using the media. Thus, the educational snakes and ladders game media was declared valid, practical, and effective in improving the literacy and numeracy skills of elementary school students.